A revised technology-organisation-environment framework for brick-and-mortar retailers adopting m-commerce - Mateus Vicente Justino; Robertson Khan Tengeh; Michael Twum-Darko (Journal of Risk and Financial Management, 2022)
This paper argues that brick-and-mortar retail Small and Medium Enterprises (SMEs) can benefit significantly from the capabilities of mobile commerce (m-commerce) to respond to the unpredictable changes in the business environment, accommodate new consumer experiences, boost sales of products/services, and achieve a competitive advantage. Consequently, this study explored the potential application of the Technology-Organisation-Environment (TOE) framework for m-commerce by brick-and-mortar retail SMEs. The study adopted the positivist paradigm and followed a cross-sectional study design. A structured questionnaire was used to collect data from a sample of 263 retail business personnel. The Analysis of Moment Structures (AMOS) software was used to analyse the data. The findings unveil that all the proposed constructs associated with the organisational context and technological context are critical for the use of m-commerce. The proposed framework provides a fresh set of contextual variables which align with brick-and-mortar retailer operations and mobile commerce practices. It is envisaged that the extended framework may help conventional businesses to understand and identify the requisite factors in the adoption and use of m-commerce and assist business supporters in the process of technological innovation transfer.
Keywords: 650; retailer; Angola; brick-and-mortar retailer; Luanda; mobile commerce (m-commerce); mobile technology; retailing; Small and Medium Enterprises (SMEs); Technology– Organisation– Environment (TOE)